The Implications of Ultrasound (USG) Technology and Pregnancy Tests Kit on the Relevance of the ‘Iddah Period from the Perspective of the Maqashid Shariah - Lilia Prasastiningtyas; Lely Mahartina Khoiru Ummah; Diyan Putri Ayu (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
The technical meaning of ‘iddah, according to the majority of scholars, is the waiting period observed by a woman to ascertain the purity of her womb, for the purpose of worship or to observe a period of mourning following the death of her husband. ‘Iddah is not an original Islamic custom but a pre-Islamic one. However, Islam has retained it as an obligation whilst modifying certain provisions that were not in accordance with logical principles. With the development of medical equipment (ultrasound) and pregnancy tests, it cannot be denied that the rationale behind the obligation of ‘iddah for a woman needs to be re-examined, as the previous rationale no longer aligns with the developments of the modern era. The rationale of ‘iddah is no longer merely about ascertaining the purity of the womb from a fetus or child, but there are higher wisdom and reasons beyond that. These include honoring the bond of marriage, as well as serving as an act of worship to Allah and obedience to His commands. The research method chosen for this study is library research. This method aims to gather data, opinions and information regarding the ‘iddah and technological advancements with the aid of various materials available in the library, such as books and notes relating to the main issue raised by the author. This study employs both a Sharia-based and a historical approach. The results of the literature review conducted by the author indicate that various medical tools, including ultrasound (ultrasonography) and pregnancy test kits, both of which can detect pregnancy with great accuracy cannot eliminate the obligation of the ‘iddah period, as in-depth research has revealed that the obligation of the ‘iddah for women is not merely to ascertain the emptiness of the womb which can be determined quickly with the advancement of modern technology but rather there are many other underlying reasons and wisdom contained within it.